Some discussions on bone fracture in fattening swine [after slaughtering] - Miyazaki, A; Yonezawa, T; Kawashima, R. (Kyoto Univ. (Japan). Coll. of Agriculture) (Japanese Journal of Swine Husbandry Research (Japan), 1982)
Bone fracture in fattening swine has become a subject of concern in some central wholesale markets in Japan in recent years. The details of the troubles and etiological factors of the bone fracture have been investigated in the present study. The frequency of bone fracture in fattening swine in major meat wholesale markets over half a year since October 1978 has been investigated. The results revealed that the frequency of the bone fracture in all the commercial carcasses in Kyoto market amounted to 0.88% and the regions of the fracture were fourth lumbar vertebra or femur, whereas the frequency of bone fracture in Tokyo wholesale market was so low as 0.06% of all the slaughtered number and the regions of the fracture were concentrated into four extremities. There has been no incident of bone fracture in the carcasses in Osaka wholesale market, which was therefore out of question there. The findings on the fracture in Kyoto market suggested an overload upon carcasses by a high-speed rolling of slaughtered body in a large heavy duty depilation machine during the skinning in hot water, whereas it was assumed in the cases of skinning for Tokyo wholesale market that the lesser incidents of fracture and its concentration into the legs may be attributable to the different type of skinning machines in Tokyo and the incidents in Tokyo would be attributable to the manner of handling and transportation of fattening swine. The frequency of incidents of fracture in fattening swine shipped into and slaughtered at the Kyoto central market varied with the eight swine operation areas in the range from 0.11 up to 3.22%. The survey on the rearing conditions of fattening swine in these operation areas in terms of the causes for the differences in the incidents of fracture revealed that the frequency of bone fracture was higher in fattening swine where garbage containing as much as 30% stale bread or bread sippets in the dry matter of feeds are fed, and besides that excessive amount of sweetened bread was being supplied to the swine. It was assessed that excessive ingestion of sugars, shortage in calcium and much higher ratio of phosphorus to calcium in feedstuffs must have caused fragility of bone. It should be further pointed out that elasticity coefficients of bone vary with individual fattening swine even though they are kept under the same conditions. It was therefore assumed that, of the fattening swine with generally poorer skeletal structure due to inadequate feeding conditions, those under some aggravated, conditions may have developed the bone fracture when subjected to skinning with hot water and with high-speed rotations by the skinning machines after the slaughter.